Profesi Penyuluh Agama diantara Dinamika Realita Sosial Keagamaan - Aziza, Aulia (UIN Antasari Banjarmasin, 2014)
The emergence of tendencies of religious violence and ethnic conflicts in some parts of Indonesia, increasingly threaten the future of the nation and society that is known to be very pluralistic. The violence of course, should not be allowed to flourish. It can not be separated from each element of the nations efforts to find a way out of the threat of religious and ethnic conflict. From the above statement, this paper will examine some of the issues related to religious education in a pluralistic society. Questions posed to the problem is: Why does the exclusiveness in religious life happen? What solution is offered to confront religious exclusivism, especially in the context of pluraliss?